Loss of PHD3 in myeloid cells dampens the inflammatory response and fibrosis after hind-limb ischemia - Beneke, Angelika (Cell Death Dis, 2017)
Macrophages are essential for the inflammatory response after an ischemic insult and thereby influence tissue recovery. For the oxygen sensing prolyl-4-hydroxylase domain enzyme (PHD) 2 a clear impact on the macrophage-mediated arteriogenic response after hind-limb ischemia has been demonstrated previously, which involves fine tuning a M2-like macrophage population. To analyze the role of PHD3 in macrophages, we performed hind-limb ischemia (ligation and excision of the femoral artery) in myeloid-specific PHD3 knockout mice (PHD3(−/−)) and analyzed the inflammatory cell invasion, reperfusion recovery and fibrosis in the ischemic muscle post-surgery. In contrast to PHD2, reperfusion recovery and angiogenesis was unaltered in PHD3(−/−) compared to WT mice. Macrophages from PHD3(−/−) mice showed, however, a dampened inflammatory reaction in the affected skeletal muscle tissues compared to WT controls. This was associated with a decrease in fibrosis and an anti-inflammatory phenotype of the PHD3(−/−) macrophages, as well as decreased expression of Cyp2s1 and increased PGE2-secretion, which could be mimicked by PHD3(−/−) bone marrow-derived macrophages in serum starvation.